Glycine Promotes the Survival of a Subpopulation of Neural Stem Cells - Bekri, Abdelhamid; Drapeau, Pierre (Frontiers in Cell and Developmental Biology, 2018)
Glycine is mainly known as an inhibitory neurotransmitter in adult mature neurons, regulating neuronal network activity in the central nervous system. In contrast, during embryogenesis glycine can act as an excitatory neurotransmitter and generates the first electrical signal in immature neurons. The roles and functional significance of this excitatory glycinergic activity during neurodevelopment are still unclear. Using the zebrafish embryo as a model, we previously showed that glycine regulates proliferation and differentiation of neural stem cells (NSCs) to interneurons. Moreover, we identified that glycine signaling in NSCs is associated with several common developmental pathways and surprisingly also the p53-related apoptosis. Here we investigated how glycine signaling regulates NSC survival. First, we showed by two approaches, acridine orange staining and active caspase 3 immunostaining that defects in glycine signaling induce an early and transient cell death, which was suppressed by knockdown of p53. Then, we developed an NSC transplantation strategy to directly assess NSC-autonomous development upon perturbing glycine signaling. In vivo time-lapse imaging showed that disruption of glycine signaling disturbed the normal NSC interkinetic nuclear migration, leading to cell cycle arrest and apoptosis. Finally, we analyzed two main subpopulations of NSCs, expressing either nestin or GFAP, by in situ labeling and in transgenic lines expressing GFP in either population. We found that disruption of glycine signaling induced a drastic and selective loss of nestin-positive (nestin+) NSCs, which was only partially rescued upon p53 knockdown. Taken together, our findings support a role of glycine signaling in promoting survival of the nestin+ NSC subpopulation early during development.